Antibiotic use and the development of inflammatory bowel disease: a national case/control study in Sweden - Nguyen, Long H. (Lancet Gastroenterol Hepatol, 2020)
BACKGROUND: Early life antibiotics have been linked to childhood inflammatory bowel disease (IBD), but data on adults is mixed—particularly for ulcerative colitis (UC)—and is based on smaller investigations that have not assessed risk among siblings with shared genetic/environmental risk factors. Our objective was to determine the association of antibiotic therapy and IBD in a large, population-based investigation. METHODS: We conducted a population-based prospective case-control study of individuals aged ≥16 years in ESPRESSO (Epidemiology Strengthened by histoPathology Reports in Sweden), the Swedish Patient Register, and the Prescribed Drug Register to identify all consecutive cases of incident IBD (2007–2016) based on histology and ≥1 diagnosis code for IBD or its subtypes: UC and Crohn’s disease (CD). Cumulative antibiotic dispensations accrued until one year prior to the time of matching for both study cases and up to five general population controls matched on the basis of age, sex, county, and calendar year. We also included unaffected full siblings as a secondary control group. Conditional logistic regression was used to estimate multivariable-adjusted odds ratios (aORs) and 95% confidence intervals (CIs). FINDINGS: We identified 23,982 new IBD cases (15,951 UC, 7,898 CD, 133 IBD-unclassified), 28,732 siblings, and 117,827 controls. Prior use of antibiotics (never vs. ever) was associated with a nearly two-times increased risk of IBD after adjusting for several risk factors (aOR 1·94, 95% CI: 1·85–2·03). Compared to none, one (aOR 1·11, 95% CI: 1·07–1·15), two (aOR 1·38, 95% CI: 1·32–1·44) , and ≥three antibiotic dispensations (aOR 1·55, 95% CI: 1·49–1·61) were associated with increased odds of IBD compared to controls. Increased risk was noted for UC and CD with the highest estimates corresponding to broad-spectrum antibiotics. Notably, comparable, but attenuated results were observed when siblings served as the referent (aOR 1·35, 95% CI: 1·28–1·43). INTERPRETATION: Higher cumulative exposure to systemic antibiotic therapy, particularly those with greater spectrum of microbial coverage, may be associated with an increase in risk for new-onset IBD and its subtypes. The association between antimicrobial treatment and IBD did not appear to differ when comparably predisposed siblings were used as the referent controls. FUNDING: National Institutes of Health; Crohn’s and Colitis Foundation